2007
DOI: 10.1007/s00261-007-9294-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular cancer response to radiofrequency tumor ablation: contrast-enhanced ultrasound

Abstract: Radiofrequency ablation (RFA) is increasingly being used as percutaneous treatment of choice for patients with early stage hepatocellular carcinoma (HCC). An accurate assessment of the RFA therapeutic response is of crucial importance, considering that a complete tumor ablation significantly increases patient survival, whereas residual unablated tumor calls for additional treatment. Imaging modalities play a pivotal role in accomplishing this task, but ultrasound (US) is not considered a reliable modality for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 97 publications
1
45
1
1
Order By: Relevance
“…Although not statistically significant, this finding may be related to data reported by Park et al concerning a more rapid growth rate of new HCC nodules in patients treated with RFA compared with nontreated HCC, suggesting the need for shorter follow-up intervals in the first group compared with the second [13]. However, it should be noted that the group of patients who did not develop new HCC nodules in our series had a substantially shorter follow-up period, [16,17]. Meno univoci sono i dati riportati in letteratura riguardo i fattori di rischio della recidiva intraepatica a distanza dell'HCC.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although not statistically significant, this finding may be related to data reported by Park et al concerning a more rapid growth rate of new HCC nodules in patients treated with RFA compared with nontreated HCC, suggesting the need for shorter follow-up intervals in the first group compared with the second [13]. However, it should be noted that the group of patients who did not develop new HCC nodules in our series had a substantially shorter follow-up period, [16,17]. Meno univoci sono i dati riportati in letteratura riguardo i fattori di rischio della recidiva intraepatica a distanza dell'HCC.…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, all the above confirms the advantage of following up patients treated with RFA with an imaging modality, such as MDCT, which is able to visualise the entire hepatic parenchyma. Other modalities, such as contrast-enhanced US, may be useful for assessing treatment effectiveness - especially during the interventional procedure -but they have few or no indications for detecting new HCC foci during the follow-up [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…CAs increases the procedure's efficiency by a better visualization of the tumor and by correct guidance of the ablation needle in the active (vascularized) area of the tumor (Skjoldbye et al, 2002, Lencioni et al, 2004. After ablative procedures, or even better in one month after the procedure, the absence of the circulation bed in the tumor in arterial phase suggests an effective treatment Vilana et al, 2006, Bartolotta et al, 2008. This principle is also true for chemotherapy with antiangiogenic agents.…”
Section: Discussionmentioning
confidence: 97%
“…Even under these conditions combination of CEUS with i.v. contrast CT examination is required to detect small metastases between procedures (Bartolotta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, ablative margin width .5 mm after RFA was considered as safe "disease-free margin". 24 A sufficient safe margin can greatly decrease the local tumour recurrence rate, whereas with the ablative margin width of ,5 mm, secondary RFA should be performed to ensure complete ablation. 22 Among the included studies, only two studies 15,22 have reported the complete ablated rate based on safe margin width.…”
Section: Discussionmentioning
confidence: 99%